Study on the Modification Effect of Side Pot And Diffuser to the Aerodynamics of the F1 IN SCHOOLS Car - Faiz Paturrahman, Mohamad; Radzi Abu Mansor, Mohd; Harun, Zambri; Anas Mohd Sabri, Mohd (International Journal of Engineering and Technology, 2018)
The F1 IN SCHOOLS competition was established in 2004 to develop studentsâ€™ interest towards science, technology, engineering and mathematics (STEM) in the secondary school phase. The application of aerodynamics is one of the important aspects studied during this phase. There are two factors that must be considered in the analysis affecting the aerodynamic performance of the car, namely the maximum velocity of the drag coefficient and the downforce coefficient. The F1 IN SCHOOLS car velocity is mainly related to its aerodynamic design and features. The objective of this paper is to study the effect of different side pot and diffuser designs that are capable of producing a low drag coefficient while maintaining a sufficient downforce coefficient. The simulation study was conducted using CFD STAR CCM+ software. The results will help to produce a miniature car that will meet two important criteria of low drag coefficient and sufficient downforce coefficient.Â Â